2019
DOI: 10.1103/physreva.100.042303
|View full text |Cite
|
Sign up to set email alerts
|

Search by lackadaisical quantum walks with nonhomogeneous weights

Abstract: The lackadaisical quantum walk, which is a quantum walk with a weighted self-loop at each vertex, has been shown to speed up dispersion on the line and improve spatial search on the complete graph and periodic square lattice. In these investigations, each self-loop had the same weight, owing to each graph's vertex-transitivity. In this paper, we propose lackadaisical quantum walks where the self-loops have different weights. We investigate spatial search on the complete bipartite graph, which can be irregular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…We do this by finding the eigenvectors and eigenvalues of U = SCQ for large N using degenerate pertur- bation theory, expressing the initial state in this eigenbasis, and then evolving the state by multiplying each eigenvector by its eigenvalue. This proves that some of the symmetry of the graph can be broken while preserving the speedup, as for the regular complete bipartite graph [21]. Proving the general case with every self-loop taking a different value, as in Fig.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…We do this by finding the eigenvectors and eigenvalues of U = SCQ for large N using degenerate pertur- bation theory, expressing the initial state in this eigenbasis, and then evolving the state by multiplying each eigenvector by its eigenvalue. This proves that some of the symmetry of the graph can be broken while preserving the speedup, as for the regular complete bipartite graph [21]. Proving the general case with every self-loop taking a different value, as in Fig.…”
mentioning
confidence: 71%
“…Lackadaisical quantum walks with nonhomogeneous weights were introduced for searching complete bipartite graphs [21], where the self-loops in one partite set had one weight, and the self-loops in the other partite set had another weight. Regular complete bipartite graphs are vertex transitive, and although the nonhomogeneous weights broke this symmetry, not all the symmetry was broken, as vertices within a partite set still evolved identically.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The three-state quantum walk has been demonstrated to increase the success probability of quantum search tasks from 50% to 100%. Wong has shown that lazy three-state quantum walk on a two-dimensional grid are faster than their acyclic counterparts when searching for marked vertices [21]. Additionally, Rhodes and Wong have developed a numerical expression for self-loop appropriate weights in undirected quantum walk spatial search [22].…”
Section: Introductionmentioning
confidence: 99%